Economic Struggle and Social Ties: The Structure of Competitive Relationships in New Russian Retail Market - Radaev, Vadim (Journal of Economic Sociology, 2010)
In conventional economic theories competing ﬁ rms are assumed to act independently. Economic sociology, on the contrary, describes competition not as a set of antagonistic moves of independent actors but as a social action oriented toward others. It implies that competing ﬁ rms which are not supposed to transact with one another establish social ties and maintain complex institutional arrangements to sustain in the market. Accepting these sociological insights, we have to avoid oversocialized concepts of competition. It means that the idea of social embeddedness of competitive actions should be tested empirically. It is also important to investigate a variety of existing forms of the interﬁ rm social coordination. In this paper I suggest a taxonomy of social ties. Using empirical data, I reveal the scope, multiplicity, and intensity of these ties among the competitors, and examine conditions which could facilitate or derail coordinated actions in the market.Data were collected from 500 managers of retailing chains and their suppliers in ﬁ ve Russia’s cities including Moscow, S.-Petersburg, Yekaterinburg, Novosibirsk, and Tyumen in autumn 2007. The sample includes transnational com